Chemical Vapor Deposition for Solvent‐Free Polymerization at Surfaces. Issue 3 (27th November 2012) - Yagüe, Jose Luis; Coclite, Anna Maria; Petruczok, Christy; Gleason, Karen K.
Abstract Chemical vapor deposition (CVD) methods are a powerful technology for engineering surfaces. When CVD is combined with the richness of organic chemistry, the resulting polymeric coatings, deposited without solvents, represent an enabling technology in many different fields of application. This article focuses on initiated chemical vapor deposition (iCVD), a new technique that utilizes benign reaction conditions to yield conformal and functional polymer thin films. The latest achievements in coating surfaces and 3D substrates with functional materials, and the use of the technique for biotechnology and selective permeation applications are reviewed, and future directions for iCVD technology are discussed.